Pengaruh Rasio Keuangan terhadap Pembiayaan Murabahah pada Bank Muamalat Indonesia - Naurah Azhaar Humaira; Dede Riswandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2026)
This study aims to analyze the effect of Third Party Funds (DPK), Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF) on murabahah financing at Bank Muamalat Indonesia during the 2020–2024 period. This research employed a quantitative approach with an associative research design. The data used were quarterly financial statements of Bank Muamalat Indonesia from 2020 to 2024 obtained through documentation methods. The sampling technique applied was saturated sampling in which the entire population was used as the research sample. Data analysis was conducted using multiple linear regression with the assistance of EViews 14 software and classical assumption tests. The results indicate that Third Party Funds (DPK), Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF) have a positive effect on murabahah financing. Meanwhile, Capital Adequacy Ratio (CAR) has no effect on murabahah financing. The coefficient of determination shows that the independent variables explain 91.77% of murabahah financing. The implication of this study suggests that public fund collection and the effectiveness of financing distribution are important factors in increasing murabahah financing in Islamic banking.